Whither to Public Interest-The Curious Case of Compulsory Drug Licensing in Indian Pharmaceutical Industry - Rakesh Kumar Sehgal1 , R.L. Koul2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Countries like India which are grappling with providing healthcare to heterogeneous and varied base ofstakeholders including those at the bottom of pyramid have their own share of availability and affordabilityconcerns in the healthcare sector for providing access of life saving drugs to the vast segment of Indianpopulation and move towards the achievement of the Sustainable Developmental Goals (SDGs); in processaddressing not only adequate availability of the primary health care but achieving the competition frameworkvis- a- vis patent control as the Original Patents which intend to protect innovation tangentially run across theconsequential price determination power by monopolistic patented drug companies. Compulsory licensing ofPatents provisions are used by the Governments as a means to correct anti-competitive practices to promotepublic interest or public health and in cases of emergency avoiding monopolies at the hands of patent holdersto deter anti-competitive violations by engaging in unfair competition or abuse of dominant position in themarket which aspect is so crucial to provide outreach of cheaper and quality drugs in common good.